Liver kinetic growth rate predicts postoperative liver failure after ALPPS. Issue 10 (October 2016) - Kambakamba, Patryk; Stocker, Daniel; Reiner, Cäcilia S.; Nguyen-Kim, Thi Dan; Linecker, Michael; Eshmuminov, Dilmurodjon; Petrowsky, Henrik; Clavien, Pierre-Alain; Lesurtel, Mickael
Abstract: Background: Posthepatectomy liver failure (PHLF) may occur after ALPPS (Associating liver partition and portal vein ligation for staged hepatectomy) despite a sufficient standardized future liver remnant (sFLR) volume. The aim of this study was to test kinetic growth rate (KGR) after ALPPS stage 1, describing the percentage increase of sFLR per day, as a predictor of PHLF after completion of ALPPS. Methods: The ability of KGR to predict PHLF after ALPPS stage 2 was investigated in 38 patients. PHLF was defined according to the "50–50" and ISGLS criteria. Results: Completion of ALPPS was achieved in 95% (36/38) of patients. The incidence of PHLF was 22% (8/36) and 36% (13/36) according to "50–50" and ISGLS criteria, respectively. Whereas a sFLR cut off at 30% alone failed to predict PHLF, KGR ≥6%/day after stage 1 was associated with a significant reduced risk of PHLF ("50–50", p = 0.03/ISGLS, p = 0.03) after stage 2. Adherence to both concomitant KGR ≥6%/day and sFLR ≥30% reduced the incidence of PHLF to 0%. Conclusions: Assessment of KGR is a novel tool to estimate the risk of PHLF after ALPPS. Respecting KGR and sFLR after ALPPS stage 1 may increase safety in patients undergoing ALPPS.